2021
DOI: 10.1159/000519847
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Icotinib, an EGFR Tyrosine Kinase Inhibitor in Non-Small Cell Lung Cancer Patients with Exon 19 Deletion and Exon 21 L858R: A Retrospective Analysis in China

Abstract: <b><i>Introduction:</i></b> The effect of icotinib on non-small cell lung cancer (NSCLC) patients with <i>EGFR</i> exon 19 deletions (19-Del) or L858R point mutation in exon 21 (21-L858R) remains inconsistent. This study aimed to evaluate the efficacy and safety of icotinib in patients with advanced NSCLC harboring these 2 <i>EGFR</i> mutations. <b><i>Methods:</i></b> We retrospectively assessed the clinical effects of first-line icotinib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In our study, female patients, those with a history of surgery, a history of radiotherapy, an EGFR-19del mutation, or an ECOG performance status score of 0-1 had an observed progression-free survival bene t, which occurred both in patients administered with almonertinib and in those receiving osimertinib. We also noticed a greater bene t of EGFR-TKI in the EGFR-19del compared to the EGFR-L858R mutant population, which also suggests the greater propensity of the EGFR-L858R mutant population to EGFR-TKI resistance [5,20]. In a subgroup analysis, we reported shorter PFS with almonertinib compared to osimertinib in patients without the EGFR-T790M mutation but not in patients with the EGFR-T790M mutation.…”
Section: Discussionmentioning
confidence: 50%
“…In our study, female patients, those with a history of surgery, a history of radiotherapy, an EGFR-19del mutation, or an ECOG performance status score of 0-1 had an observed progression-free survival bene t, which occurred both in patients administered with almonertinib and in those receiving osimertinib. We also noticed a greater bene t of EGFR-TKI in the EGFR-19del compared to the EGFR-L858R mutant population, which also suggests the greater propensity of the EGFR-L858R mutant population to EGFR-TKI resistance [5,20]. In a subgroup analysis, we reported shorter PFS with almonertinib compared to osimertinib in patients without the EGFR-T790M mutation but not in patients with the EGFR-T790M mutation.…”
Section: Discussionmentioning
confidence: 50%
“…In this cohort, nearly 52% (48/92) of patients carried the EGFR L858R mutation. A previous study has shown that patients harbored EGFR 19_Del confers lower PFS with icotinib than those harbored EGFR L858R mutations [ 26 ]. Therefore, the distribution of EGFR L858R and EGFR 19_Del may be the cause of a shorter PFS than previous studies.…”
Section: Discussionmentioning
confidence: 99%